OSU AEROSPACE INSTITUTE AS AN EDUCATIONAL AND SCIENTIFIC TRAINING CENTER FOR DEFENSE INDUSTRY ENTERPRISES - Anatoliy I. Serdyuk; Alexander N. Polyakov; Aleksey B. Radygin (Высшее образование в России)
The article describes the areas of cooperation between the OSU Institute of Aerospace and an industrial enterprise “Strela”, which became a partner of the university in the scientific, educational and financial sectors of engineers training and retraining. There have been marked out successes and mutually beneficial areas of cooperation, such asmodernization of resource and technical base of the institute, skills upgrading and vocational retraining of the enterprise’ workers, co-participation in grant competitions. The authors also formulate directions for further development of partnership.